2005
DOI: 10.1158/1078-0432.ccr-04-1676
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial and Pharmacokinetic Study of Raltitrexed in Children with Recurrent or Refractory Leukemia: A Pediatric Oncology Group Study

Abstract: Purpose: To evaluate the toxicity, antileukemic activity, and pharmacology of raltitrexed administered weekly for 3 weeks to patients with refractory or recurrent leukemia.Experimental Design: Raltitrexed was administered as a 15-minute infusion for 3 consecutive weeks every 5 weeks, at doses ranging from 1.3 to 2.8 mg/m 2 . The first course was used to determine the dose-limiting toxicities and maximum tolerated dose. Correlative studies included an assessment of raltitrexed pharmacokinetics and measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The maximum increase of dUrd level was observed on day 2 following which plasma dUrd gradually returned to baseline by day 8, suggesting that TS inhibition was short-lived with this schedule of pemetrexed. This pattern is comparable to previous studies with the classical anti-folate raltitrexed (RTX), which showed dUrd elevations on days 1 -3 and which returned back to baseline within 2 weeks of treatment (Ford et al, 2002;Horton et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The maximum increase of dUrd level was observed on day 2 following which plasma dUrd gradually returned to baseline by day 8, suggesting that TS inhibition was short-lived with this schedule of pemetrexed. This pattern is comparable to previous studies with the classical anti-folate raltitrexed (RTX), which showed dUrd elevations on days 1 -3 and which returned back to baseline within 2 weeks of treatment (Ford et al, 2002;Horton et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Accumulation of dUMP occurs as a direct consequence of TS inhibition and also as a result of increased activity of other enzymes, including ribonucleotide reductase (RR) and deoxycytidylate (dCMP) deaminase (Maybaum et al, 1981). A number of studies have indicated that plasma dUrd is an important pharmacodynamic (PD) marker of TS inhibition (Mitchell et al, 1997;de Jonge et al, 2002;Ford et al, 2002;Rees et al, 2003) especially with the use of the TS inhibitors AG337 (Nolatrexed) (Jodrell et al, 1999;Estlin et al, 2001), ZD9331 (de Jonge et al, 2002;Ford et al, 2002;Rees et al, 2003) and ZD1964 (raltitrexed) (Ford et al, 2002;Horton et al, 2005); however, similar studies have not been performed with pemetrexed.…”
mentioning
confidence: 99%
“…We answered to these questions positively, taking advantage of two antifolate selective inhibitors of the synthesis of purine or pyrimidine DNA precursors, such as LY309887 [ 21 , 22 ] and raltitrexed (TDX) [ 22 ], respectively. These compounds display potent activity against human leukemia cells [ 23 – 26 ], and may turn out to be effective agents for the clinical treatment of leukemia [ 27 ]. LY309887 is a folate analogue that selectively inhibits glycinamide-ribonucleotide-formyl-transferase (GARFT) [ 28 ], while TDX selectively targets thymidylate-synthase (TS) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive laboratory and clinical use has identified tumors that have intrinsic or acquired resistance to methotrexate 1, 2. Novel agents that maintain antifol cytotoxic effects but have unique biochemical properties that alter resistance patterns and toxicity profiles have been developed 3–5. One such antifol, pemetrexed (Alimta), has been approved for the treatment of non‐small cell lung cancer and, in combination with cisplatin, for the treatment of malignant pleural mesothelioma 6, 7.…”
Section: Introductionmentioning
confidence: 99%